(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2020)
Stemming from the importance role of the teaching staffs with the development of the education sector in general and higher education in particular, the application of Ho Chi Minh’s thoughts on teachers to improve ability of the teaching staffs to meet the increasing demands of society is an essential issue today.